Effect of Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), Current Ratio (CR), Net Profit Margin (NPM) and Earning Per Share (EPS) on Stock Prices - Muhammad Rafi; Sri Rahayu; Muhammad Ridwan (Indonesian Journal of Economic & Management Sciences, 2023)
The purpose of this research is to examine and verify the impact of Return on Assets, Return on Equity, Debt to equity ratio of manufacturing companies, current ratio, net profit margin, and earnings per share related to stock prices focusing on the cement subsector and listed for 2016– 2021 on the Indonesia Stock Exchange. The sample analysis carried out in this study involved 5 companies, with observations made for 6 years from 2016 to 2021. The data used came from secondary sources, namely the company's annual financial statements downloaded from the IDX's official website. The research strategy for data analysis is multiple linear regression. The results of the study show that individually, Earning Per Share has an influence on stock prices, but Return on Assets, Return on Equity, Debt to Equity Ratio, Current ratio, net profit margin, and stock prices do not seem to be connected